CO-CREATION-HF protocol: clinical trial to evaluate the impact of a comprehensive and hybrid cardiac rehabilitation model on patients with heart failure - Pamela Seron; Daniela Gómez-Pérez; Edgardo Opazo-Díaz; Maria Jose Oliveros; Maria Francisca Contreras; Alejandra Salinas; Omar Andrade-Mayorga; Gabriel Nasri Marzuca-Nassr; Kathleen Saavedra; Cinthya Espejo; Sergio Muñoz; Fernando Lanas; et al. (Frontiers in Cardiovascular Medicine)
IntroductionComprehensive, hybrid cardiac rehabilitation (CR) models have been scantly investigated in heart failure (HF) populations, particularly in low-resource settings. CO-CREATION-HF aims to evaluate the effectiveness of such a model compared to supervised exercise alone.Methods and analysisA 2 parallel-arm, multi-center randomized clinical superiority trial will be conducted with blinded outcome assessment. 152 HF patients (NYHA class II or III) will be recruited consecutively, and randomly assigned using permuted blocks; allocation will be concealed. The 12-week intervention will include evaluation, medical and nurse management, aerobic interval training, resistance exercise training, psychosocial support, and education. These will initially be delivered in a center, transitioning to home in 4 stages. Controls will receive similar management, but face-to-face continuous aerobic exercise sessions and resistance exercises. The main outcomes are cardiorespiratory fitness (VO2 max), functional capacity (m from 6 MWT), and quality of life (Minnesota Living with Heart Failure Questionnaire). Program adherence and completion, NT-proBNP, functioning, all-cause and HF-specific mortality and hospitalization, muscle strength, adverse events and cost will be secondary outcomes. These will be measured at baseline, end of intervention, and 12-month follow-up. The sample size was calculated considering 90% power, a significance level of 5%, a between-group difference equivalent to 1/2 MET, and a 10% potential loss to follow-up. Intention-to-treat analysis will be considered. Between-group differences will be assessed using Student's t-tests or Z-tests along with 95% confidence intervals, and the rate ratio will be computed to compare mortality.Ethics and disseminationThe study protocol and the Informed Consent form were approved by Ethical Committees at the Universidad de La Frontera (No. 081-23) and each center participating. Research findings will be disseminated to the scientific community and will be shared with relevant stakeholder groups and policy-makers. Finally, investigators shall reach HF patients via various dissemination channels such as social media. Clinical Trial Registrationclinicaltrials.gov, identifier (NCT06313684).